Leadership Theories and Leadership in Healthcare Facilities - İbrahim Gün; Özgür Aslan (Association of Nurse Managers, 2018)
Business management processes consist of planning, organizing, leading and controlling. After organizing functions, leadership is a crucial concept in the real world where things are actually done and results are produced. Since the beginning of clinical medicine, there have been leaders who have grown up the next generation of health care professionals and academics. Because the effective leadership offered by health professionals has vital importance to modern health management. The underlying factor behind this is demand for high quality and effective healhcare services. Clinicians undertaking leadership roles need to overcome the quality barriers and adopt a leadership style that meets the needs of inclusive services and health professionals. When leadership approaches are examined in general, they are classified as trait approaches, behavioral approaches, situational approaches and contemporary approaches. To be able to accomplish organizational goals across changing paradigms and to be able to preserve its existence in the long run are the main goals of organizations. Not to make mistakes in the allocation of resources is highly depends on professional managers who can coordinate within the organization by providing leadership. As in other sectors, leadership in the healthcare sector and affects of leaders are extremely important in influencing and directing subordinates.